Agriculture in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Edited by C C Webster & P N Wilson. Blackwell Science. 1999. 552 pp.ISBN 0 632 04054 8.£69.50 Euro 108.60Vivienne Harvey, Blackwell Science,Osney Mead, Oxford OX2 0EL, UK.Fax: + 44 1865 721 205